2022
DOI: 10.3390/w14101604
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of South African Brewery Wastewater: Oxidation-Reduction Potential Variation

Abstract: Conventional wastewater treatment processes are challenged by the need to effectively reduce pollutant loads before disposal or reuse, as the composition and concentration of contaminants in brewery wastewater change with time. This results in the variation of the oxidation-reduction potential (ORP) of the affluent. Hence, the current study is aimed at the application of ORP as a real-time tool to monitor brewery wastewater quality. Other physicochemical parameters of the local brewery in South Africa investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The ORP is an indicator reflecting the redox status of the water or soil (Li et al, 2004;Gao et al,2002). An ORP value greater than 0mV indicates an oxidative medium, while a value less than 0mV indicates a reducing medium (Khumalo et al, 2022). In this study, it was found that the ORP of the overlying water in YZN was less than 0mV, indicating its reducing nature.…”
Section: Correlation Analysis Between Water Environmental Factors And...mentioning
confidence: 58%
See 1 more Smart Citation
“…The ORP is an indicator reflecting the redox status of the water or soil (Li et al, 2004;Gao et al,2002). An ORP value greater than 0mV indicates an oxidative medium, while a value less than 0mV indicates a reducing medium (Khumalo et al, 2022). In this study, it was found that the ORP of the overlying water in YZN was less than 0mV, indicating its reducing nature.…”
Section: Correlation Analysis Between Water Environmental Factors And...mentioning
confidence: 58%
“…The ORP is an indicator reflecting the redox status of the water or soil (Li et al, 2004; Gao et al,2002). An ORP value greater than 0mV indicates an oxidative medium, while a value less than 0mV indicates a reducing medium (Khumalo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that high SD values mean that the value of the measured physiochemical property lies generally far from the mean, while low SD values mean the measured physiochemical property values are clustered close to the mean. Moreover, the SD was calculated by reducing the sample size from n to n − 1, this was implemented to avoid a biased estimate when using a sample size of n, thus underestimating the variability [37].…”
Section: Discussionmentioning
confidence: 99%
“…In the optimization of microbial fuel cell (MFC) systems, the relationship between the oxidation-reduction potential (ORP) and pH play a crucial role in understanding and enhancing system performance. ORP (mV) intricately indicates the electron transfer potential within the MFC environment [46,[56][57][58][59]. pH, on the other hand, measures the acidity or alkalinity of the solution, influencing microbial activity and electrochemical reactions [20,25,58,60,61].…”
Section: Rsm-bbd Application For Optimized Orp (Mv) Vs Ph Correlation...mentioning
confidence: 99%